Partial characterization of Onion yellow dwarf virus from onion in India - and R.P. PANT*, N.V. HOA, Y.S. AHLAWAT (Indian Phytopathology, 2003)
A disease similar to onion yellow dwarf was observed in onion seed crop during 1995-1996.The incidence of the disease ranged from 51.74%to 89.98% in three IARI fields of onion seed crop during 1998-1999.Pure culture of virus was obtained by mechanical and aphid transmission to onion seedlings. The virus purified from glass-house inoculated onion plants had filamentous particles ranging from 650-900 nm. However, maximum particles were of 775 nm in size. Polyclonal antibodies were raised in rabbit and used for detection of the virus by ELISA and ISEM. iSEM studies revealed that the field affected plants carried mixed infection of two filamentous viruses, but the glasshouse inoculated plants carried only one virus. The virus was serologically related to Banana bract mosaic virus, Potato virus V and Onion yellow dwarf virus but not to Brinja/ mosaic viruse, Cowpea aphid borne mosaic virus, Henbane mosaic virus and Peanut stripe virus. The virus has been identified as an isolate of Onion yellow dwarf virus from India.